Implementing Japanese PMA Organizational Culture in Indonesia impacts Employee Job Satisfaction, Employee Performance and Employee Retention of Japanese and Indonesian Employees - Martadinata Martadinata; Evi Susanti; Rina Anindita (Research Collaboration Community (RCC), 2022)
The expansion of Japanese parent companies worldwide has forced them to carry the organizational culture that the Japanese founders had held onto their overseas subsidiaries. The main purpose of study is examined organizational culture, employee job satisfaction, and employee performance of Japanese PMA companies in Indonesia on employee retention. Eight Japanese companies were used as the sample, where 33 Japanese employees and 222 Indonesian employees were respondents. Theory Z is used to discuss organizational culture. The questionnaire was made in Indonesian, English, and Japanese. The research model uses a tiered structure model, while to test the proposed hypothesis, the SEM Lisrel 8.8 analysis technique is used. The main finding is the organizational culture of Japanese companies in Indonesia strongly influences job satisfaction, employee performance, and employee retention. Applying Japanese corporate culture shows that Japanese and Indonesian employees understand the company's core values. Employee performance can be realized by employees being able to understand the cultural values of the organization.